Right ventricle in hypoplastic left heart syndrome exhibits altered hemodynamics in the human fetus. (9th November 2020) - Zebhi, Banafsheh; Wiputra, Hadi; Howley, Lisa; Cuneo, Bettina; Park, Dawn; Hoffman, Hilary; Gilbert, Lisa; Yap, Choon Hwai; Bark, David
Abstract: Hypoplastic left heart syndrome (HLHS) represents approximately 9% of all congenital heart defects and is one of the most complex, with the left side of the heart being generally underdeveloped. Numerous studies demonstrate that intracardiac fluid flow patterns in the embryonic and fetal circulation can impact cardiac structural formation and remodeling. This highlights the importance of quantifying the altered hemodynamic environment in congenital heart defects, like HLHS, relative to a normal heart as it relates to cardiac development. Therefore, to study human cardiovascular fetal flow, computational fluid dynamic simulations were performed using 4D patient-specific ultrasound scans in normal and HLHS hearts. In these simulations, we find that the HLHS right ventricle exhibits a greater cardiac output than normal; yet, hemodynamics are relatively similar between normal and HLHS right ventricles. Overall, this study provides detailed quantitative flow patterns for HLHS, which has the potential to guide future prevention and therapeutic interventions, while more immediately providing additional functional detail to cardiologists to aid in decision making.